The Laying Rooster Performance Fed with the Addition Indigofera Leaf Meal-based Diet - Somanjaya, Rachmat; Widianingrum, Dini; Wardaya, Yaya (Universitas Halu Oleo, 2022)
This study aimed to evaluate the effect of Indigofera leaf meal (ILM) and to measure the optimum composition of the addition of ILM in the diet on the performance of layer roosters. The study conducted experiments on 100-layer roosters of the Cobb strain. The experimental design used a completely randomized design (CRD) with four treatments and five replications, each replication with five chicks. The treatments were R0 (100% commercial feed or non-ILM); R1 (90% commercial feed + 10% ILM); R2 (80% commercial feed + 20% ILM); and R3 (70% commercial feed + 30% ILM). The data were processed by analysis of variance (ANOVA one way) and further tested by Duncan's multiple range test (DMRT). The results showed that the addition of 10% ILM in the diet could increase (P<0.05) feed consumption and average daily gain and could provide a lower feed conversion and feed cost per gain value (P<0.05) than R0. Treatment R2 and R3 did not have a better impact than treatment R0 (P>0,05). It can conclude that adding 10% Indigofera leaf meal to the diet can have a good effect on the performance of layer roosters.Keywords: indigofera leaf meal, layer rooster, performance